Kebaya dan Budaya Populer: Pembentukan Identitas Ideologis Perempuan Modis oleh Kapitalis - Suraya, Rahmat Sewa; Rustiani, Komang Wahyu; Suseno, Sandy (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 2 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONALDO - 10.24843/JIWSP.2023.v05.i02.p08, 2023)
Balinese Kebaya is a custom clothing used by women when there is a Yadnya ceremony and even used simultaneously by the community on Thursday and Tilem Purnama. Mode Kebaya very quickly changes; almost every week, a new mode appears. Balinese women do not realize that Kebaya in fact the form of adoption of an external culture that blends in the consequences of the past trade. Balinese women do not realize that there is capitalist ideology in the movement of fashion Kebaya in Bali. This research is important to do to reveal the psychology of women in use kebaya Bali and reveal fashion ideology kebaya towards Balinese women. This research is examined using postmodern theory with an ideology approach that is described descriptively and qualitatively. The results show that the following mode, kebaya, is a representation of social class among Balinese women. Balinese women tend to be prestige wearing monotone kebaya. If there is a large special ceremony like Odalan (usually implemented once a year), then Balinese women, especially in Padambulia, feel obliged to have a new kebaya by following the fashion that was trending at that time. The capitalists succeeded in building a fashionable ideology on women with a very rapid change of fashion in order to control the market.